Primary myocardial fibrosis - a distinct entity characterized by heterogeneous histology - Pakanen Lasse; Appel Henrik; Ahtikoski Anne; Holm Pernille Heimdal; Kreus Mervi; Olsen Kristine Boisen; Banner Jytte; Winkel Bo Gregers; Huikuri Heikki; Kaarteenaho Riitta; Junttila Juhani (Elsevier Inc., 2025)
Primary myocardial fibrosis (PMF), defined as myocardial fibrosis in the absence of identifiable causes, may represent a common alternative phenotype in various cardiomyopathies and contribute to sudden cardiac death (SCD). No previous definitions of histopathological characteristics exist for PMF. We aimed to evaluate whether common features of fibrosis could be identified. PMF cases (n = 28) were selected from the FinGesture cohort consisting of 5,869 SCD victims that underwent a medicolegal autopsy. Twelve trauma controls and 10 ischemic heart disease cases were selected as reference groups. Further 3 PMF cases and 5 ischemic heart disease cases from autopsies performed in the University of Copenhagen, Denmark, were selected for a validation substudy. Relative area of fibrosis, amount of diffuse and perivascular fibrosis, and location of fibrosis were assessed from left ventricle myocardial samples stained with Masson trichrome. Further evaluations were performed with alpha-smooth muscle actin (α-SMA), vimentin, and CD68 stainings. Mean relative area of fibrosis was 5.8 ± 10.7%, 1.0 ± 0.7%, and 7.0 ± 7.4% in PMF, trauma controls, and ischemic cases, respectively. Fibrosis in the PMF group was mostly located in other sites than the endocardium. Most cases with fibrosis had vimentin-positive but α-SMA-negative stromal cells within fibrotic areas. Histopathologically, PMF represents a heterogeneous entity with variable fibrotic lesions affecting the whole myocardium and a suggested significant role of fibroblasts. These findings may bring validation to PMF being a common manifestation of cardiomyopathies. Evidently, PMF stands out as a particular entity demanding special attention as a cause of SCD.